2021
DOI: 10.21037/apm-21-2109
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the application of vascular endothelial growth factors in preeclampsia

Abstract: Background: Hypertensive disorders of pregnancy (HDP) is a disease associated with elevated blood pressure during pregnancy, accounting for 5-10% of all pregnancies, which includes: gestational hypertension, preeclampsia (PE), eclampsia, chronic hypertension with superimposed PE and chronic hypertension. PE is the most prevalent type of HDP that seriously threatens the life and health of mothers and infants. In-depth exploration of the pathogenesis can play an early role in predicting the disease.Methods: A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…VEGF is part of the endothelial growth factor family consisting of VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F, PGF, and endocrine gland-derived VEGF (EG-VEGF) [73,74]. VEGF interacts with receptor 1 (VEGFR1 (Flt1)) and receptor 2 (VEGFR2 (KDR/FlK1)) to carry out its functions and is a key protein in the neural and vascular development of the brain [28,75].…”
Section: Vascular and Angiogenic Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is part of the endothelial growth factor family consisting of VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F, PGF, and endocrine gland-derived VEGF (EG-VEGF) [73,74]. VEGF interacts with receptor 1 (VEGFR1 (Flt1)) and receptor 2 (VEGFR2 (KDR/FlK1)) to carry out its functions and is a key protein in the neural and vascular development of the brain [28,75].…”
Section: Vascular and Angiogenic Dysregulationmentioning
confidence: 99%
“…VEGF interacts with receptor 1 (VEGFR1 (Flt1)) and receptor 2 (VEGFR2 (KDR/FlK1)) to carry out its functions and is a key protein in the neural and vascular development of the brain [28,75]. When binding to VEGF-R2, VEGF regulates the development of morphological features of cerebral blood vessels and vascular permeability [76,77], as well as the dendrogenesis and somatogenesis of Purkinje cells [73,[78][79][80][81][82]. For example, given that VEGF is a signal for neuronal migration and a facilitator of the stimulation of action potentials, it has been suggested that a decrease in the expression of this factor-for example, at the cerebellar level-could deregulate the molecular signaling cascades involved in vascular restructuring, synapses, and, therefore, functional processes.…”
Section: Vascular and Angiogenic Dysregulationmentioning
confidence: 99%
“…PlGF is predominantly expressed in the placenta and has a major role in the development and maturation of the placental vascular system. PlGF supports trophoblast growth, and low levels of PlGF are a marker for abnormal placentation, which is seen in preeclampsia [19,20]. Figure 1 shows that patients with preeclampsia have lower levels of circulating PlGF concentrations than those without preeclampsia.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Hypertensive disorders of pregnancy (HDP) are a group of diseases including gestational hypertension (GH), preeclampsia (PE), pregnancy complicated with chronic hypertension, chronic hypertension complicated with pre-eclampsia (Liu et al 2021. Patients may be accompanied by systemic multiple organ dysfunction, such as renal insufficiency, liver damage, nervous system, and blood system complications (Joo et al 2021).…”
Section: Introductionmentioning
confidence: 99%